PERLINDUNGAN HUKUM TERHADAP PEREMPUAN YANG BEKERJA DI MALAM HARI DI HOTEL NIKKI DENPASAR - Andriani, Arik; Dharma Kusuma, A A Gede Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013, 2013)
In daily activities, women are forced to work to fit their life. It will affect that they have to add their working time. The result should be undergone by them who work at night are sex abuse and even rape. Based on the description, writer writes these problem. The problems are how the implementation of law safety for women who work at night and the factors which affects the implementation of law safety for women who work at Hotel Nikki Denpasar, The purpose in this article is for defemine the implement of law safety for women who work at night and the factor which affects.
Keywords: law protection, women asiss